2022
DOI: 10.31083/j.jin2104117
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic System Function in Patients with Transient Global Amnesia

Abstract: Background:The purpose of this study was to examine glymphatic system function in patients with transient global amnesia (TGA), as well as to conduct a recurrence analysis. Methods: We enrolled patients with TGA and healthy controls from our hospital retrospectively. The patients and healthy controls were all scanned with the same 3T scanner, which included diffusion tensor imaging (DTI). We investigated the function of the glymphatic system using DTI analysis along the perivascular space (DTI-ALPS). The ALPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This is a common finding in healthy volunteers and in neurodegenerative diseases such as Parkinson's and Alzheimer's disease. However, in cases of brain tumors [9][10][11], REM sleep disorder [46], neuromyelitis optica [47], renal disease [48,49], global amnesia [50], and migraine [36] did not find significant correlation was found between DTI-ALPS and age. In our research, we did also not find any correlation between patients' age and DTI-ALPS index.…”
Section: Discussionmentioning
confidence: 87%
“…This is a common finding in healthy volunteers and in neurodegenerative diseases such as Parkinson's and Alzheimer's disease. However, in cases of brain tumors [9][10][11], REM sleep disorder [46], neuromyelitis optica [47], renal disease [48,49], global amnesia [50], and migraine [36] did not find significant correlation was found between DTI-ALPS and age. In our research, we did also not find any correlation between patients' age and DTI-ALPS index.…”
Section: Discussionmentioning
confidence: 87%
“…This might indicate that there is a relationship between the brain network alterations and EEG findings in patients with TGA. Furthermore, we recently demonstrated that the glymphatic system function differed significantly according to TGA event recurrence, 35 being higher in patients with recurrent TGA events than in those with a single event. These previous findings along with the present results suggest that the pathophysiology of patients with recurrent TGA events differ from that of patients with one TGA event.…”
Section: Discussionmentioning
confidence: 99%